Bi‐supported Ziegler–Natta TiCl4/MCM‐41/MgCl2 (ethoxide type) catalyst preparation and comprehensive investigations of produced polyethylene characteristics. Issue 15 (15th October 2019) - Jafariyeh‐Yazdi, Elchin; Tavakoli, Akram; Abbasi, Farhang; Parnian, Mohammad Javad; Heidari, Amin
ABSTRACT: Bi‐supported Ziegler–Natta catalysts (TiCl4 /MCM‐41/MgCl2 (ethoxide type)) were synthesized to improve the morphology and the properties of polyethylene. The morphology control is a crucial issue in polymerization process, while tailoring the properties of polymers is needed for specific applications. The catalysts were synthesized in different ratios of two supports with impregnation method. The polymerization process was carried out in atmospheric slurry reactor. The catalysts were characterized with scanning electron microscopy ‐ energy dispersive X‐ray spectroscopy (SEM–EDX), inductively coupled plasma, Fourier transform infrared spectrometry (FTIR), and Brunauer‐Emmett‐Teller (BET) methods. The polymers were analyzed with scanning electron microscopy (SEM), thermogravimetric analysis (TGA), differential scanning calorimetry, FTIR, and tensile‐strength analyses. Ubbelohde viscometer and frequency sweep measurements showed that the synthesized polymers are ultra‐high‐molecular‐weight polyethylene. Mechanical properties of polymers showed higher Young's modulus in samples containing MCM‐41, having higher thermal stability supported by TGA analysis. SEM images of bi‐supported catalyst showed a controlled spherical morphology with uniform size distribution. SEM analysis support that the polymers replicate their morphology from catalyst, improving their morphology comparing to MgCl2 ‐supported catalyst. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48553. Abstract :